Research of the Design of Double Helical Gear Modification based on KISSsoft Software - Yang Shuowen; He Di; Tang Jinyuan; Wan Guoxin (Jixie chuandong)
Based on the KISSsoft software,the modification parameters of double helical gear are designed and researched. The performance indexes such as the transmission error,the normal force and the tooth surface load distribution are used to evaluate the modification parameters and the relation between performance indexes and design parameters of gear is given. Considering the effect of axis parallelism deviation and torque,the design of transverse profile modification and flank line modification of double helical gear is researched and then the design flow of modification parameters of double helical gear based on KISSsoft software is given. Taking one pair of double helical gear in an industry as an example,the original modification parameters are redesigned and optimized to solve large transmission error,load concentration of tooth surface and large normal force. Compared with the original modification parameters,the transmission error and the load concentration of tooth surface can be reduced and the normal force is decreased by the optimized modification parameters. The research show that,using KISSsoft software to optimize the modification parameters could avoid the traditional complicated optimization design flow by repeatedly rolling inspection and optimizing parameters.